Evaluation of Storage and Freezing, Baking, and Boiling Treatments on Total Carotenoids Content in the Fruits of Selected Cucurbita moschata Duch. Varieties - Adriána Maťová; Alžbeta Hegedűsová; Alena Andrejiová; Ondrej Hegedűs; Marcel Golian; Miroslav Šlosár; Judita Lidiková; Tomáš Lošák (Journal of Food Quality)
Cucurbita moschata Duch. is a seasonal crop, appreciated for its nutrimental and bioactive components especially carotenoids. From the whole edible plant, fruit is most often consumed which can be stored and also processed. Six varieties—Liscia, Matilda, Orange, Serpentine, UG 205 F1, and Waltham—of Cucurbita moschata Duch. were investigated, in order to analyze and evaluate the changes in total carotenoids content in the pulp during storage and after the effect of heat treatments—freezing, baking, and cooking (water boiling). The average total carotenoids content ranged from 3.32 mg/100 g (Serpentine) to 9.35 mg/100 g fresh matter (FM) (Orange). After 60 days of storage, a slight increase in the total carotenoids content of all analyzed varieties was observed. The values of the monitored varieties ranged from 4.18 mg/100 g FM (Serpentine), which represents a 26% increase to 10.96 mg/100 g FM (Orange), where a 17% increase was observed. After 120 days of storage, the results were mixed. In some varieties (Liscia and Matilda), the total carotenoid content decreased, while in the varieties Serpentine, UG 205 F1, and Waltham, its content increased slightly (11%, 3%, and 11%), but the content of the Orange variety remained unchanged. The total carotenoids increment after 60 and 120 days of storage in the dry matter (DM) was statistically significant, as well as the effect of the variety. The total carotenoid content of cooked samples of all varieties increased, from 119.78 mg/100 g DM (Waltham) to 255.19 mg/100 g DM (Orange). After baking, an average of 12% increase in the total content of carotenoids was recorded, after freezing, a decrease in its level of 5% was indicated. The findings of this work show that Cucurbita moschata Duch. is a good source of carotenoids, even after several weeks of storage and after exposure to heat treatments.